The Concept of Language and Its Acquisition Stages - Hazaymeh, Omar; Al-Jawarneh, Adam; Jarrah, Mufleh; Battah, Monther (Journal of Asian Multicultural Research for Social Sciences Study, 2024)
Modern linguistics interests are no longer limited to the theoretical and analytical aspects of language, but new interests have been added to them - especially after the emergence of applied linguistics - aimed at serving the community, and among these tasks are: the interest in studying articulation defects, speech problems, the child's linguistic development, language acquisition, and communication skills besides other topics that have a close relationship to language and society. Language is a very complex system, and although children use their first language effectively before they even enter school, they acquire the complex system of language without teaching because they should not be taught how to speak. The present study aims to investigate the concept of language and its acquisition stages besides its forms and conditions.